2020
DOI: 10.1192/j.eurpsy.2020.71
|View full text |Cite
|
Sign up to set email alerts
|

Early onset of cannabis use and violent behavior in psychosis

Abstract: Background: Although evidence from psychosis patients demonstrates the adverse effects of cannabis use (CU) at a young age and that the rate of CU is high in subgroups of young violent patients with psychotic disorders, little is known about the possible effect of the age of onset of CU on later violent behaviors (VB). So, we aimed to explore the impact of age at onset of CU on the risk of displaying VB in a cohort of early psychosis patients. Method: Data were collected prospectively ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
1
6
0
5
Order By: Relevance
“…On this line, a recent Swiss cohort study on an early psychosis population of 265 patients found that the earlier the cannabis abuse started, the higher was the risk of physical aggressiveness [99].…”
Section: ••]mentioning
confidence: 97%
See 1 more Smart Citation
“…On this line, a recent Swiss cohort study on an early psychosis population of 265 patients found that the earlier the cannabis abuse started, the higher was the risk of physical aggressiveness [99].…”
Section: ••]mentioning
confidence: 97%
“…Cannabis abuse has been confirmed as a risk factor for violence in a Swiss investigation on patients with early psychosis. The combination of cannabis use, impulsivity, lack of insight, and non-adherence to treatment furtherly increased the risk [99].…”
Section: ••]mentioning
confidence: 99%
“…A three‐step hierarchical multiple regression analysis was then performed to identify the most important clinical covariates of aggression scores in the patients group. Alcohol and cannabis use (Kudumija Slijepcevic et al, 2014; Moulin et al, 2020; Oueslati et al, 2018), as well as other factors including DUP, insight and psychotic symptoms (Nielssen et al, 2012) have been shown to be strongly associated with aggression and violence in patients with psychotic disorders, and were thus added as covariates. For this, aggression scores were taken as a dependent variable and other variables (age, gender, alcohol and cannabis use, age of onset of illness, DUP, functioning, psychopathology, insight, impulsiveness and psychopathy) were used as independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, patients with schizophrenia who report substance use have a confirmed increased risk of aggression (Faay & Sommer, 2021). Particularly, alcohol (Kudumija Slijepcevic et al, 2014) and cannabis (Moulin et al, 2020) have been shown to be among the strongest predictors of violent behaviours in schizophrenia. Furthermore, multiple clinical risk factors have been reported, such as a younger age at illness onset, more severe psychotic symptomatology (Caqueo‐Urízar et al, 2016), and a longer duration of untreated psychosis (Rund, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It seems also that dose-response ( 39 , 46 , 60 , 61 ), trajectory of consumption ( 56 ), and persistence of CU ( 39 ) could be important variables in the association between CU and VB. In studies conducted in prisoners ( 53 ) and in the general population ( 61 ), it has been shown that the average age at which the violent patients started using cannabis was 15 years [two years earlier than the non-violent patient group ( 62 )], and that the precocity of CU was a risk factor for VB ( 62 ) .…”
Section: Cannabis Use and Violent Behavior In The Early Phase Of Psyc...mentioning
confidence: 99%